Generation of reference serum proteome map for monitoring swine health - DE, ANKAN; ALI, MOHAMMAD AYUB; BEHERA, PARTHASARATHI; CHUTIA, TUKHESWAR; DAS, HEMEN; HMAR, LALNUNTLUANGI; GALI, JAGAN M OHANARAO (The Indian Journal of Animal Sciences, 2020)
To the best of our knowledge, it is the first report on pig serum proteome map generated with LAPs enriched serum using nano ESI LC-MS/MS method. A total of 224 proteins were identified including several proteins not yet reported in earlier pig serum proteome maps. Moreover, identification of many intracellular proteins indicates their usefulness in determination of altered cell functionality. Altogether, the identified proteins in our study can serve as baseline prerequisite for future analytical studies to understand different patho-physiological conditions in pigs.